The interplay of EFL teachers' immunity, work engagement, and psychological well-being: Evidence from four Asian countries - Wang, Yongliang; Derakhshan, Ali; Azari Noughabi, Mostafa (Journal of multilingual and multicultural development, 2024)
Due to the novelty of the concept of language teacher immunity, conceptualised as a robust armouring system that helps language teachers cope with threats to their well-being, scant multi-cultural research has been dedicated to the investigation of its correlates. The present study seeks to explore the interplay of immunity, psychological well-being, and work engagement among 1135 English as a foreign language (EFL)teachers from four Asian countries. The data were collected through three questionnaires. The results of structural equation modelling (SEM) analysis indicated that Asian EFL teachers' psychological well-being and work engagement positively influenced their immunity. Additionally, the findings indicated that psychological well-being was a better predictor of teacher immunity than work engagement in Asia. The results, discussed in the light of positive psychology (PP), highlight language teachers' need for working in a psychologically healthy environment to remain committed to their job and immune to its difficulties.